(untitled) (Educação e Pesquisa, 2023)
Active methodologies break away from the teaching centered on the hierarchical transmission of knowledge from the teachers to the student, helping perfect the teachinglearning process centered on the student. This study aimed to investigate the contributions of a discipline based on active methodologies to the academic, personal, and professional development and to the meaningful learning of the students-monitors, both regarding scientific knowledge in the study of topics of Movement Sciences and regarding the initiation to research. This is a qualitative narrative research, in which we investigate de development of the student-monitors by using reports of the self and of the lived experience as they participated in a discipline of introduction to scientific methodology and the study of Movement Sciences. We assumed, for the analysis of the constructed data, the textual and discursive analysis (TDA), evidencing the research and reflection about the learning of the student-monitors during the discipline “Experimenting sciences: the human body in movement.” The data were collected with a questionary, via Google Forms. Based on textual and discursive analysis, the following categories emerged: i) reflections about the personal and academic development; ii) construction of scientific knowledge; iii) critical posture regarding learning and professional conduct/perspective. We concluded that, with the pedagogical strategy used in the discipline, centered on the active methodologies, aiming at the initiation to research, the group of student-monitors manifested academic and personal development, construction of scientific knowledge, and meaningful learning When orienting, under supervision of the teachers, groups of students in experiments about the human body in movement.